Fine structure of the ductuli efferentes of the hamster (Mesocricetus auratus). - Vicentini, Carlos Alberto [UNESP]; Orsi, A. M.; Gregório, E. A. (My University, 1990)
Structurally the ductuli efferentes of the hamster showed 2 distinct segments, a testicular and an epididymal. Both of these segments were lined by a pseudostratified epithelium, which showed basically non-ciliated and ciliated cells. In the testicular segment a 3rd type of oval dark cells was observed. The ultrastructural characteristics of these cells were presented and discussed in this report.
Keywords: animal; electron microscopy; epididymis; hamster; histology; male; testis; ultrastructure; Animal; Epididymis; Hamsters; Male; Mesocricetus; Microscopy, Electron; Testis